Magnesium supplementation and iron status among female students: the intervention study: Magnesium supplementation and iron status - Milinković, Neda (Journal of Medical Biochemistry, 2021)
Background: Literature data indicate the benefit of magnesium (Mg) supplementation. The aim of this study was to examine the effect of short-term Mg supplementation on iron status in healthy female participants. Methods: One hundred healthy female students of the University of Belgrade - Faculty of Pharmacy participated in the study during eleven intervention days. Students ingested Mg preparations with the same dose of the active substance. The analysis included the measurement of serum iron, unsaturated iron binding capacity (UIBC), total iron binding capacity (TIBC), total Mg (tMg), ionized Mg (iMg), complete blood count, met-, carboxy- and oxy-haemoglobin (metHgb, COHgb, O2Hgb). Transferrin concentrations and the percentage of transferrin saturation (SAT) were calculated manually. The association among the analyzed biochemical parameters was examined using polynomial regression. A principal component analysis (PCA) was used for the evaluation of interdependence between the analyzed parameters. Results: A statistically significant trend for change in O2Hgb (%) by tertiles of iMg concentrations was found (P = 0.029). Serum tMg reached a significant positive correlation with the SAT at concentration levels greater than 0.9 mmol/L, after 11 days of intervention (R2=0.116). Ionized Mg in a concentration higher than 0.6 mmol/L is positively correlated with SAT and serum Fe (R2=0.214; 0.199, respectively). PCA revealed variability of 64.7% for two axes after 11 days. Conclusions: Mg supplementation leads to an improvement in certain iron status parameters even in individuals with optimal levels of these indices. However, caution should be exercised when supplementing Mg, and laboratory monitoring of the interaction is required.